A Wireless Passive Conductivity Detector for Fluidic Conductivity Analyzation in Microchannel - Hoang, Bao Anh; Nguyen, Canh Viet; Tran, Thi Thuy Ha; Pham, Van Thanh; Do, Trung Kien; Chu, Duc Trinh; Bui, Thanh Tung; Do, Quang Loc (JST: Engineering And Technology For Sustainable Development, 2021)
Electrical conductivity is one of the main parameters of an electrolyte solution. Fluidic conductivity detection and analyzation is very important in many academic research and industrial applications. In order to avoid the issues of the conventional sensing technique, this study utilizes the wireless passive conductivity detector for fluidic conductivity analyzation in the microchannel. The operation of the proposed structure is designed, simulated and then validated by experiments. The experimental results show that the resonance frequency of the sensor decreases from 64.7 MHz to 58.6 MHz according to the rise of KCl concentration in the fluidic channel from 10 mM to 1 M. The dependence of resonance frequency on the distance between inductors was also implemented and analyzed in this work. The integration of the LC passive sensing technique in microfluidic conductivity detector can be utilized in various academic research, industrial application, especially in biosensor applications.